Answer:
Step-by-step explanation:
9^8 to 9^10 involves a change (multiplication) of 9^8 by 9^2 (which is 81).
Over the given interval, f(x) increases by 81.
Answer:
D
Step-by-step explanation:
So we have the expression:
![(3x^2-5x+6)+(9-8x-4x^2)](https://tex.z-dn.net/?f=%283x%5E2-5x%2B6%29%2B%289-8x-4x%5E2%29)
Combine like terms:
![=(3x^2-4x^2)+(-5x-8x)+(6+9)](https://tex.z-dn.net/?f=%3D%283x%5E2-4x%5E2%29%2B%28-5x-8x%29%2B%286%2B9%29)
Add or subtract:
![=(-1x^2)+(-13x)+(15)](https://tex.z-dn.net/?f=%3D%28-1x%5E2%29%2B%28-13x%29%2B%2815%29)
Simplify:
![=-x^2-13x+15](https://tex.z-dn.net/?f=%3D-x%5E2-13x%2B15)
Our answer is D
Answer:
13 units
Step-by-step explanation:
D is at (1,6) and C is at (-4,-6)
The distance is found by
d = sqrt(( y2-y1)^2+ (x2-x1)^2))
= sqrt( ( -6-6)^2 + (-4-1)^2)
= sqrt( -12^2 + -5^2)
= sqrt( 144+ 25)
= sqrt( 169)
= 13
(7.2 × 10^7) ÷ (9 × 10^4)
= (7.2 / 9) x 10^(7 - 4)
= 0.8 x 10^3
= 8 x 10^2
Answer
C. 8 × 10^2